Nanoparticles of beetroot extract: A potential antimalarial adjuvant in Plasmodium berghei-infected mice - Fransisca Pramesshinta Hardimarta; Lisyani Budipradigda Suromo; Kis Djamiatun (Journal of Advanced Biotechnology and Experimental Therapeutics)
Malaria disease is caused by a variant of mosquitoes that leads to transmission in humans. This study aimed to investigate the effects of beetroot extract (NBE) nanoparticles on parasitemia index and ICAM-1 levels in mice infected with Plasmodium berghei. Thirty male mice were randomly divided into six groups including H= baseline (normal/healthy), NC= P. berghei inoculation, PC= P. berghei inoculation treated with artemisinin, T1= P. berghei inoculation treated with artemisinin and NBE (50 mg/kg), T2= P. berghei inoculation treated with artemisinin and NBE (100 mg/kg), and T3= P. berghei inoculation treated with artemisinin and NBE (200 mg/kg). Parasitemia index in groups T2 (13.1%) and T3 (12.5 %) were significantly lower compared to groups NC (36 %) and PC (16.2 %). Furthermore, ICAM-1 levels in groups T2 (145.72 ng/ml) and T3 (151.24 ng/ml) were significantly lower compared to groups NC (319.17 ng/ml) and PC (241.93 ng/ml). The findings of the study suggest that nanoparticles of beetroot extract could have potential as an anti-inflammatory and antimalarial adjuvant for malaria infection. [ J Adv Biotechnol Exp Ther 2025; 8(1.000): 55-63]